In-depth study of intra-Stark spectroscopy in the x-ray range in relativistic laser–plasma interactions. (22nd November 2017) - Oks, E; Dalimier, E; Faenov, A Ya; Angelo, P; Pikuz, S A; Pikuz, T A; Skobelev, I Yu; Ryazanzev, S N; Durey, P; Doehl, L; Farley, D; Baird, C; et al.
Abstract: Intra-Stark spectroscopy (ISS) is the spectroscopy within the quasistatic Stark profile of a spectral line. The present paper advances the ISS-based study of the relativistic laser–plasma interaction from our previous paper (Oks et al 2017 Opt. Express 25 1958). By improving the experimental conditions and the diagnostics, it provides an in-depth spectroscopic study of the simultaneous production of the Langmuir waves and of the ion acoustic turbulence at the surface of the relativistic critical density. It demonstrates a reliable reproducibility of the Langmuir-wave-induced dips at the same locations in the experimental profiles of Si XIV Ly-beta line, as well as of the deduced parameters (fields) of the Langmuir waves and ion acoustic turbulence in several individual 1 ps laser pulses and of the peak irradiances of 1–3 × 10 20 W cm −2 . Besides, this study employs for the first time the most rigorous condition of the dynamic resonance, on which the ISS phenomenon is based, compared to all previous studies in all kinds of plasmas in a wide range of electron densities. It shows how different interplays between the Langmuir wave field and the field of the ion acoustic turbulence lead to distinct spectral line profiles, including the disappearance of the Langmuir-wave-induced dips.